The Metaverse: A new digital frontier for consumer behavior - Hadi, Rhonda; Melumad, Shiri; Park, Eric S. (Journal of Consumer Psychology, 2024)
AbstractThis work offers a multidisciplinary perspective on the Metaverse, focusing on its potential implications for consumer behavior. We begin by proposing a conceptualization of the Metaverse as being uniquely defined by the convergence of five key elements—it is digitally mediated, spatial, immersive, shared, and operates in real‐time. We then discuss how these components might collectively alter our understanding of consumer behavior in three domains: consumer identity, social influence, and ownership. We conclude by outlining an agenda for future research to help broaden our understanding of the Metaversal marketplace and its impact on consumer behavior. This work serves as a starting point to characterize a shift that is unfolding in the marketplace and to consider, through a consumer behavior lens, the numerous changes it may bring.